122k views
1 vote
How do you solve this problem

How do you solve this problem-example-1
User Gacon
by
6.0k points

1 Answer

6 votes

Answer:

(-6,1)

Explanation:

-x + y = 7 [Equation (1)]

2x + 5y = -7 [Equation (2)]

Multiplying equation (1) by 5, to make the coefficients of y equal in both equations.

5(-x + y) = 5(7)

=> -5x + 5y = 35 [Equation (3)]

Subtracting equation (3) from equation (2).

(2x + 5y) - (-5x + 5y) = -7 - 35

=> 2x + 5y + 5x - 5y = -7 - 35

=> 7x = -42

=> x = -42/7

=> x = -6

Putting the value of x in equation (1).

-(-6) + y = 7

=> 6 + y = 7

=> y = 7 - 6

=> y = 1

So, x = -6 and y = 1.

User Vijay Angelo
by
6.0k points